23 ESTABLISHING THE SPECIFIC CONTRIBUTION OF ADHERENT AND INVASIVE ESCHERICHIA COLI TO THE ONSET OF INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Kittana, Hatem; Gomes-Neto, João Carlos; Heck, Kari; Sughroue, Jason; Muñoz, Rafael Segura; Cody, Liz A; Xian, Yibo; Mantz, Sara; Schmaltz, Robert; Hostetter, Jesse; Clarke, Jennifer; Kachman, Steve; et al.
Abstract: Objective: Adherent and invasive Escherichia coli (AIEC) appear to expand during inflammation and are observed in the ileal mucosa in subsets of Crohn's patients. However, AIEC pathogenesis is poorly understood and cause-effect relationships between AIEC and IBD remain to be established. Importantly, a systematic comparison to determine whether in vitro phenotypes frequently used to define AIECs correlate with and predict a strain's ability to contribute to disease in vivo has yet to be performed. Design: We utilized a combination of in vitro and in vivo models to segregate 30 mucosa-associated human-derived E. coli strains into distinct phenotypic classes. In vitro assays measured survival in J774 macrophages and TNF-α production, as well as invasion and replication in Caco2 intestinal epithelial cells. A gnotobiotic mouse model assessed the ability of stably colonized strains to contribute to inflammation in vivo . Results: E. coli strains with an in vitro AIEC phenotype consistently caused more severe intestinal inflammation in mice than those with an in vitro non-AIEC phenotype. In vitro replication in J774 and Caco2 cells was positively correlated with AIEC-induced disease. Co-colonization with non-AIEC strains ameliorate AIEC-intestinal inflammation. Conclusion: Our findings establish a causative role for AIEC in exacerbating intestinal inflammation. Moreover, we demonstrate for the first time that the in vitro characteristics commonly used to identify AIEC strains can be linked to the inflammatory potential of these strains in mice. Such knowledge is an important foundation for characterizing patient E. coli isolates that may ultimately be used to better predict, diagnose and treat disease.